Experimental Study for the Integration of an Innovative Air Distribution System in Operating Rooms. (March 2017) - Nastase, Ilinca; Croitoru, Cristiana; Dan, Mircea; Ursu, Ioan; Meslem, Amina
Abstract: Hospital buildings in general and especially the operating rooms are a challenge for building services engineers which are struggling to ensure indoor environmental conditions satisfying all the occupants. The requirements imposed by standards often lead to the discomfort: while surgeons require low temperatures for sanitary reasons, anesthesiologists and assistants feel uncomfortable and prefer warmer conditions. In past studies the estimated entrainment in the case of the jets issued from the lobed perforated panel was found to be greater than in the case of the standard circular perforated panel. The lobed flow offers a larger induction and a longer throw, a more uniform distribution of the flow, allowing thermal comfort improvement if such perforated panels were used. We integrated this concept of perforated air diffuser in the air distribution system referred to as "laminar flow ceiling" for the operating rooms in hospital environments. We found that the lobed perforated panel is performing better than the circular perforated panel in isothermal conditions for several volumetric flow rates. The special geometry do not generate supplementary noise as the sound pressure levels were determined for both grilles for different discharge flow rates while the pressure losses are less than 30 Pa in the velocity range which corresponds to standard application of the air diffusion.